Program Pengabdian Masyarakat: Edukasi Keselamatan Kerja dan Diversifikasi Produk Ikan di Industri Rumahan Desa Pesisir, Situbondo: Improving Occupational Safety and Health for Coastal Villagers in the Bahari Beach Region, Situbondo - Wahyuni, Sylvia Dwi; Nimah, Lailatun; Ajija, Shochrul Rohmatul; Sari, Luthfiana Aprilianita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
80% of the population of Situbondo Regency Coastal Village work as fishermen. Fluctuating fishing results cause businesses to be processed so that they can be stored to fill the void of fishing results and improve the community's economy. The potential processed fish products at Bahari Beach are processed into fish crackers by several micro business groups consisting of residents, but unfortunately, the process of making crackers in all micro business centers still does not meet the principles of good occupational safety and health and does not wear Personal Protection Equipment (PPE) when producing. This research aims to improve knowledge related to occupational safety and health in all groups of micro-business centers in the Pesisir Village area. The training method includes coordination with target partners, preparing the needs of tools and materials during the program, and preparing learning modules that will be used as a reference in program implementation. The work stage is filled with materials and demonstrations. Finally, the evaluation stage. The training participants consisted of 35 people consisting of residents of the Coastal Village of Besuki District, Situbondo Regency. The results showed that there was an increase in the results of the questionnaire from the pre-test and post-test after the training was given. Where the results of the training participants were very enthusiastic and able to practice making rengginang and shredded fish by the principles of occupational safety and health.